2010
DOI: 10.1007/s10529-010-0433-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of acetic acid tolerance and fermentation performance of Saccharomyces cerevisiae by disruption of the FPS1 aquaglyceroporin gene

Abstract: The FPS1 gene coding for the Fps1p aquaglyceroporin protein of an industrial strain of Saccharomyces cerevisiae was disrupted by inserting CUP1 gene. Wild-type strain, CE25, could only grow on YPD medium containing less than 0.45% (v/v) acetic acid, while recombinant strain T12 with FPS1 disruption could grow on YPD medium with 0.6% (v/v) acetic acid. Under 0.4% (v/v) acetic acid stress (pH 4.26), ethanol production and cell growth rates of T12 were 1.7 ± 0.1 and 0.061 ± 0.003 g/l h, while those of CE25 were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…The intake of acetic acid produces cell acidiWcation and intracellular acetate anion (CH 3 COO ¡ ) accumulation, which is involved in inhibition of the glycolytic enzymes in yeast cells [14]. At the general culture temperature of yeast (30°C), the inhibitory eVect of acetic acid on cell growth is more eVective than on fermentation performance [22,30]. In this work, both cell growth and ethanol production of original strain CE25 at 37 and 40°C were hampered by acetic acid.…”
Section: Discussionmentioning
confidence: 96%
“…The intake of acetic acid produces cell acidiWcation and intracellular acetate anion (CH 3 COO ¡ ) accumulation, which is involved in inhibition of the glycolytic enzymes in yeast cells [14]. At the general culture temperature of yeast (30°C), the inhibitory eVect of acetic acid on cell growth is more eVective than on fermentation performance [22,30]. In this work, both cell growth and ethanol production of original strain CE25 at 37 and 40°C were hampered by acetic acid.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, appropriate engineering to upregulate the sphingolipid pathway in situ may provide a readily accessible and rational means to enhance the acetic acid tolerance of industrially valuable S. cerevisiae strains, either alone or in combination with other genetic strategies that appear to improve the acetic acid tolerance of this organism [6668]. …”
Section: Discussionmentioning
confidence: 99%
“…As www.intechopen.com mentioned above, knowledge on yeast stress mechanisms in response to acetic acid has already had an impact on the construction of industrial strains with improved performance in biotechnological processes (Zhang et al, 2011). However, most studies on stress response, including the latest on the evaluation of resistance to acetic acid at a genome-wide scale, have only been focused on the ability of yeast to divide and grow in the presence of toxic agents.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it was found that deletion of FPS1, coding for an aquaglyceroporin channel, abolishes acetic acid accumulation at low pH (Mollapour & Piper, 2007). This observation was explored to improve acetic acid resistance and fermentation performance of an ethanologenic industrial strain of S. cerevisiae through the disruption of FPS1 (Zhang et al, 2011). The acetic acid-tolerance phenotype of the disrupted mutant was mainly explained by the preservation of plasma membrane integrity, higher in vivo activity of the H + -ATPase, and lower oxidative damage after acetic acid treatment.…”
Section: Introductionmentioning
confidence: 99%